DAMPAK KEBERLANJUTAN DAN DIGITALISASI TERHADAP KINERJA KEUANGAN DAN NILAI PERUSAHAAN - Karjono, Albertus; Wibowo, Edi Wahyu (POLITEKNIK LP3I JAKARTA, 2026)
The phenomenon of corporate sustainability, manifested through Environmental, Social, and Governance (ESG) and Corporate Social Responsibility (CSR) initiatives, has become a global priority, encouraging companies to integrate environmental, social, and governance criteria into their strategies and operations. Pressure from environmental protection organizations and stakeholders has made continuous improvement a crucial topic in corporate management. Positive Relationship between Sustainability and Financial Performance (FC)/Firm Value (FV): Empirical evidence supports the hypothesis that continuous CEP improvement is positively related to both accounting-based and market-based CFP financial performance. In general, sustainability performance has been shown to have a significant positive relationship with financial performance, measured by Return on Assets (ROA) and Market Value (MV/BV). This approach aligns with the social impact hypothesis and the reputation-building explanation. Strengthening Internal Governance (IAQ) in the Digital Age: Encourage research focused on the role of internal governance mechanisms (e.g., IAQ) in verifying ESG data and mitigating the risk of Greenwashing (GW). The literature review should emphasize that managers should understand and use GW as an environmental communication strategy, but should do so carefully and be supported by effective internal audit. Alternative Performance Variables: Encourage the use of more comprehensive alternative financial and sustainability performance variables, such as additional economic and social dimensions within GW, broader corporate governance functions within IAQ, or other metrics such as ROE.